Developing Tenth-Grade Students' Problem-Solving Skills in Chemistry through Deductive Learning with the DAPIC Approach - Haruethai Duangsopa; Prasart Nuangchalerm (Online Learning In Educational Research (OLER), 2024)
The authentic science classroom requires students to think and solve problems through hands-on activity. This research aims to enhance problem-solving skills in chemistry of grade 10 students through deductive learning with the DAPIC approach, with a passing criterion of 70% or higher of the total score. This research employed action research. The target group consists of 22 students from the model school of Mahasarakham University in the second semester of the academic year 2023. The data collection instruments included nine lesson plans, three sets of essay-type problem-solving tests (each comprising three questions), student interview questionnaires regarding their opinions on learning management, and observational data on problem-solving behavior in chemistry. The research findings indicated that the target group improved their problem-solving skills after learning through deductive learning with the DAPIC approach. In the first cycle, 50% of students (11 out of 22) met the passing criterion of 70%. In the second cycle, 81.82% of students (18 out of 22) passed, and in the third cycle, 95.45% of students (21 out of 22) achieved the passing criterion. It can be concluded that deductive learning with the DAPIC approach can also enhance students' problem-solving in the science classroom.